2000
DOI: 10.1080/17450390009381938
|View full text |Cite
|
Sign up to set email alerts
|

Blood cells and plasma proteins of chickens fed a diet supplemented with (1 ? 3),(1 ? 6)‐β‐D‐Glucan and enrofloxacin

Abstract: The effects of (1-->3),(1-->6)-beta-D-glucan from Saccharomyces cerevisiae and of the fluochinolone enrofloxacin were studied on red and white blood cells and plasma proteins of growing chickens up to the 35th day of life. The prominent findings within the leukocyte population on a per cent scale are: (i) increase of leukocyte count; increase of neutrophils and decrease of lymphocytes in the control and in the antibiotic group from day 17 to day 35; (ii) a minor decrease of neutrophils and no change of lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…It was observed that the source of increased in TLC is the significantly increased lymphocyte counts due to use of Alphamune®, Increased TLC in group 4 can be attributed to immunostimulation effect of compounds of Alphamune. This result was previously observed by (Fleischer et al, 2000;Acevedo et al, 2001) who recoded increased TLC with administration of MOS and b-glucan respectively. Chicken group 4 that fed on Alphamune® supplemented ration and vaccinated with NDV vaccine showed significant lower AST and ALT levels at 35 days of age (Table 8, 9).…”
Section: Resultssupporting
confidence: 85%
“…It was observed that the source of increased in TLC is the significantly increased lymphocyte counts due to use of Alphamune®, Increased TLC in group 4 can be attributed to immunostimulation effect of compounds of Alphamune. This result was previously observed by (Fleischer et al, 2000;Acevedo et al, 2001) who recoded increased TLC with administration of MOS and b-glucan respectively. Chicken group 4 that fed on Alphamune® supplemented ration and vaccinated with NDV vaccine showed significant lower AST and ALT levels at 35 days of age (Table 8, 9).…”
Section: Resultssupporting
confidence: 85%
“…However, enrofloxacin may lead to an increase in the bactericidal action of phagocytes, such as neutrophils, in pigs (Schoevers et al, 1999). It has also been shown that after enrofloxacin administration the number of lymphocytes in the peripheral blood of 17-d-old chickens was significantly higher than that in the control group (Fleischer et al, 2000). Moreover, tilmicosin, florfenicol, or enrofloxacin administration reduced the humoral immune response in poultry, but had beneficial effects on the cell-mediated immune response (Khalifeh et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Data presented in Table (2, 6 and 7) showed the results of HI titer for NDV vaccine in different chicken groups and its effect on challenge with vvNDV where group that received Inmunair® and Betapolo® showed significant higher NDV genomatric mean HI titer (6.4, 5.4) and (5.9), respectively at 35 days of age. For Betapolo® (Fleischer et al, 2000;Acevedo et al 2001) observed increased humoral response to ND with B-glucan. While Inmunair® contains LPS and inactivated cells of Propionibacterium acnes, our results agree with the observations (Flo et al, 1996).…”
Section: Resultsmentioning
confidence: 97%